Survival of Plant Growth Promoting Bacterial Inoculants in Different Carrier Materials - Sangeetha, D (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACTIn this present study, the survival of PGPR isolates was investigated by using different carrier materials. The carrier based PGPR consortium with four selected strains viz., Azospirillum lipoferum VAZS-18, Azotobacter chroococcum VAZB-6, Bacillus megaterium VBA-2, Pseudomonas fluorescens VPS-19 was prepared and the shelf life for each inoculants was studied upto six months of storage. The surviving population in the lignite based consortium was 1.64 × 108 cfu g-1 for Azospirillum lipoferum VAZS-18, 1.46 × 108 cfu g-1 for Azotobacter chrococcum, VAZB-6, 1.22 × 108 cfu g-1 for Bacillus megaterium VBA-2 and 2.01 × 108 cfu g-1 for Pseudomonas fluorescens VPS-19 after six month of storage. The surviving population in vermiculite based consortium was 4.32 × 108 cfu g-1 for Azospirillum lipoferum VAZS-18, 1.98 × 108 cfu g-1 for Azotobacter chroococcum VAZB-6, 1.14 × 108 cfu g-1 for Bacillus megaterium VBA-2 and 3.32 × 108 cfu g-1 for Pseudomonas fluorescens VPS-19 after six months of storage. In the pressmud based consortium, the surviving population was 3.25 × 108 cfu g-1 for Azospirillum lipoferum VAZS-18, 3.00 × 108 cfu g-1 for Azotobacter chroococcum VAZB-6, 2.14 × 108 cfu g-1 for Bacillus megaterium VBA-2 and 3.42 × 108 cfu g-1 for Pseudomonas fluorescens VPS-19 after six months of storage. In the alginate bead based consortium the surviving population was 64.61 × 108 cfu g-1 for Azospirillum lipoferum VAZS-18, 56.81 × 108 cfu g-1 for Azotobacter chroococcum VAZB-6, 47.83 × 108 cfu g-1 for Bacillus megaterium VBA-2 and 63.89 × 108 cfu g-1 for Pseudomonas fluorescens VPS-19 after six months of storage.